Расчет режима системы автономного электроснабжения переменного тока малой мощности - Канов, Л.Н. (Електротехніка і електромеханіка, 2011)
A calculation technique for dynamic state of an autonomous low-power ac supply system is introduced. The technique is based on preliminary analytical approximation of the solution of a nonlinear algebraic equation and numeral integration of differential equations of the system. The technique is illustrated with an example calculation of the state of a power supply system with a DC link under variable load conditions.